Composite hydrogel for promoting wound healing and preparation method thereof
By designing composite hydrogels and utilizing natural bio-based materials and inclusion complex technology, we have achieved multi-functional synergy in wound repair materials, solving the problems of single-function materials and safety hazards in existing materials, and promoting high-quality wound healing.
Patent Information
- Application Number
- CN202511839091.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-08
- Publication Date
- 2026-01-16
- Estimated Expiration
- 2045-12-08
AI Technical Summary
Existing wound repair materials have limited functionality and cannot simultaneously meet the multiple needs of biocompatibility, antibacterial protection, inflammation regulation, cell recruitment, and anti-scar repair. Furthermore, exogenous components can easily lead to bacterial resistance and safety risks.
Using a composite hydrogel and natural biological substrate as a carrier, the stability and activity of functional components are enhanced through inclusion complex technology. The outer layer precisely removes inflammatory stress, the middle layer recruits endogenous stem cells in a targeted manner, and the core uses a biomimetic structure to guide the orderly deposition of collagen, so as to achieve dynamic adaptation of the function of each layer to the wound healing sequence.
While ensuring biocompatibility, we simultaneously address infection control, inflammation regulation, and anti-scarring issues to improve wound healing quality, avoid the safety risks of exogenous components, and achieve high-quality healing throughout the entire process.
Smart Images

Figure CN121338083A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of skin dressings, and particularly relates to a composite hydrogel for promoting wound healing and a preparation method thereof. BACKGROUND
[0002] Wound repair is a key research direction in the biomedical field, especially the repair of chronic wounds and infected wounds. The repair of chronic wounds and infected wounds is a clinical difficulty due to multiple factors such as susceptibility to inflammation imbalance, infection risk, and insufficient repair cell infiltration. An ideal wound repair material needs to meet multiple requirements such as biological safety, antibacterial protection, inflammation regulation, cell recruitment, and anti-scarring repair to adapt to the dynamic healing process of wounds from the inflammation phase, proliferation phase to remodeling phase.
[0003] Current wound repair materials have the problems of single function and fragmented repair mechanism. Some materials only focus on antibacterial effect and rely on the continuous release of exogenous antibacterial agents, which can easily cause bacterial resistance and is difficult to consider cell compatibility. Some pro-healing materials rely on exogenous growth factors to activate the repair process, which not only has the defects of easy inactivation and short half-life of biological activity, but also may cause abnormal proliferation due to excessive factors. Therefore, it is a key to solve the current technical bottleneck to develop a repair material that can promote wound healing and activate repair potential. SUMMARY
[0004] In view of the defects of the prior art, the present application provides a composite hydrogel for promoting wound healing and a preparation method thereof. The composite hydrogel takes natural biological substrate as the core carrier, improves the stability and activity of functional components through inclusion technology, relies on the oxidation-sensitive characteristics of the outer layer to accurately remove inflammatory stress and provide antibacterial protection, the middle layer activates repair potential by directing the recruitment of endogenous stem cells through active peptides, and the inner core realizes anti-scarring repair by guiding the ordered deposition of collagen through biomimetic structure. The functions of each layer are dynamically adapted to the timing of wound healing. On the basis of ensuring excellent biocompatibility, the multiple contradictions of infection prevention and control, inflammation regulation, and tissue remodeling are solved. The technical problems of single function of traditional wound repair materials, easy infection, imbalance of inflammation regulation, and poor anti-scarring effect are solved, and the quality of wound healing is significantly improved.
[0005] In order to achieve the above technical purpose, the technical scheme adopted by the present application is as follows: The present application provides a composite hydrogel for promoting wound healing, which comprises the following raw materials by weight: 60-80 parts of a composite core, 3-8 parts of type I collagen, 8-15 parts of gelatin, 0.1-0.3 parts of SDF-1 alpha analog peptide (stromal cell-derived factor-1 alpha analog peptide), 25-35 parts of hyaluronic acid, and 8-15 parts of inclusion compound. The composite core comprises raw materials in the following mass ratio: Bombyx mori silk: asiaticoside = 1:0.0001-0.0002; The preparation method of the composite core comprises the following steps: (1) Boil Bombyx mori silk in a 0.5% sodium carbonate solution for 30 min, repeat twice to completely remove sericin, wash with deionized water, dry, form fibroin fibers, dissolve the fibroin fibers in a 9.3 M lithium bromide solution, the dosage ratio of fibroin fibers to lithium bromide solution is 1 g:10 mL, stir in a 60 ℃ water bath until completely dissolved, then perform dialysis treatment to completely remove lithium bromide, centrifuge to remove impurities, and obtain a clear fibroin protein aqueous solution with a mass-volume concentration of 6-8%; (2) Dissolve asiaticoside in DMSO (dimethyl sulfoxide) to prepare a stock solution with a concentration of 1-2 mg / mL, slowly drop the stock solution into the fibroin protein aqueous solution, the final concentration of asiaticoside is 10-20 μg / mL, magnetically stir for 2 hours to make it uniformly mixed, and form a mixed solution; (3) Load the mixed solution into a syringe of an electrospinning device, electrospinning forming, set the process parameters: injection speed 0.5-1 mL / h, voltage 15-20 kV, receiving distance 12-20 cm, control the environmental humidity at 40-50%, after obtaining the nanofiber membrane on the receiving plate, place it in an ethanol vapor with a volume fraction of 75% for 30 min, and obtain the composite core.
[0006] The inclusion complex comprises raw materials in the following mass ratio: hydroxypropyl-β-cyclodextrin: curcumin = 3-10:1; The preparation method of the inclusion complex comprises the following steps: (a) Dissolve hydroxypropyl-β-cyclodextrin in deionized water, the dosage ratio of hydroxypropyl-β-cyclodextrin to deionized water is 1 g:100-150 mL, and form a hydroxypropyl-β-cyclodextrin solution; (b) Dissolve curcumin in anhydrous ethanol, the dosage ratio of curcumin to anhydrous ethanol is 1 g:10-20 mL, then drop the hydroxypropyl-β-cyclodextrin solution into the curcumin solution under vigorous stirring, continue to stir in the dark for 24 h, then filter and freeze-dry to obtain the inclusion complex.
[0007] The application also provides a preparation method of a composite hydrogel for promoting wound healing, which specifically comprises the following steps: S1, dissolve type I collagen in a 0.1% acetic acid aqueous solution, stir overnight, prepare a collagen solution, dissolve gelatin in PBS (phosphate buffer, pH 7.4), and stir to dissolve in a 37 ℃ water bath, and prepare a gelatin solution; S2, the collagen solution and gelatin solution are mixed in a volume ratio of 1:1, constant temperature at 37 DEG C is gently stirred to avoid bubbles, and a mixed solution i is formed; S3, the SDF-1 alpha simulation peptide is dissolved in PBS, EDC (carbodiimide) and NHS (N-hydroxysuccinimide) are added as crosslinking agents, activated for 30 min at 4 DEG C, and an activated SDF-1 alpha simulation peptide is formed, the amount ratio of SDF-1 alpha simulation peptide, EDC, NHS and PBS is 5 mg:5-10 mg:5 mg:1-2 mL, the activated SDF-1 alpha simulation peptide is added to the mixed solution i, and slowly reacts for 12 h at 4 DEG C, so that the simulation peptide is covalently grafted to the amino group of gelatin and collagen through amide bond, and a mixed solution ii is obtained; S4, the composite core is immersed in the mixed solution ii, and then transferred to a constant temperature environment at 37 DEG C, and placed for 1 h to perform heat-induced crosslinking, so that a firm stem cell recruitment layer is formed outside the core, the surface is gently washed with PBS, and a composite is obtained; S5, hyaluronic acid is dissolved in PBS to prepare a 1% mass / volume concentration of hyaluronic acid solution, 3-(acrylamido) phenylboric acid, EDC and NHS are added to the hyaluronic acid solution, wherein the amount ratio of 3-(acrylamido) phenylboric acid, EDC, NHS and hyaluronic acid solution is 0.1-0.15 g:0.5 g:0.3 g:100 mL; avoid light reaction at room temperature for 24 h, dialysis purification, freeze-drying, and obtain oxidized hyaluronic acid; S6, the oxidized hyaluronic acid and the inclusion compound are dissolved in PBS to form a pre-gel solution, the composite prepared in step S4 is completely immersed in the pre-gel solution, and after taking out, it is placed under 365 nm ultraviolet light for 30-90 s to perform ultraviolet crosslinking reaction, so that the acrylamide groups on the oxidized hyaluronic acid chain are covalently crosslinked, and a dense antioxidant outer layer is formed outside the composite, and after being washed with PBS, then sterilized, a composite hydrogel for promoting wound healing is obtained.
[0008] Compared with the prior art, the beneficial effects obtained by the present application are as follows: The composite hydrogel prepared by the application for promoting wound healing is prepared from a composite core, a clathrate, etc., and an antioxidant outer layer is constructed with an oxidation-sensitive characteristic to build an initial protective barrier for a wound, and curcumin is preferentially released in a high active oxygen environment in the inflammation period, which can not only clear excessive active oxygen to inhibit the diffusion of inflammatory factors, but also reduce the damage risk of stem cells by reducing inflammation stress, and ensure the activity retention of the middle layer of simulated peptides. The antioxidant outer layer gradually degrades with the decrease of active oxygen level after the inflammation subsides, and starts to continuously release SDF-1 alpha simulated peptides, actively recruits endogenous stem cells to the wound, and avoids the cell infiltration obstacle caused by structural barriers; the collagen-gelatin network not only provides an attachment scaffold for the stem cells migrated to the wound after the outer layer degrades, but also precisely anchors the stem cell surface receptors through covalent grafting of the simulated peptides, and provides a nutrient transmission channel for the inner core scaffold in the slow degradation process in the proliferation period of the wound, ensuring that the active ingredients of the inner core can be gradually released with the repair process; at the same time, the cytokines secreted by the recruited endogenous stem cells can strengthen the regulation of fibroblasts by the active ingredients of the inner core. The silk fibroin scaffold of the composite core has the structural advantages of a biomimetic extracellular matrix, and its porous characteristics and the wound microenvironment exposed after the middle layer degrades are perfectly matched, providing sustained growth space for the recruited stem cells, and the asiaticoside loaded in the core precisely acts on the key node of the transition from the proliferation period to the remodeling period, which not only inhibits the excessive proliferation of fibroblasts to reduce the disordered deposition of collagen, but also forms a complement with the ordered synthesis of collagen guided by stem cells, avoiding the disadvantages of inhibiting the repair process when using existing anti-scar ingredients alone. Through the interlayer cooperation, the active ingredients are precisely released in space and time, which not only avoids the security risks of deactivation and possible abnormal proliferation of exogenous factors, but also makes the repair process more in line with the human physiological mechanism, so that the wound can complete the whole-process high-quality healing relying on its own repair mechanism without external intervention. BRIEF DESCRIPTION OF DRAWINGS
[0009] Figure 1 The anti-inflammatory situation diagram of the composite hydrogel prepared by the application for promoting wound healing; Figure 2 The free radical scavenging rate situation diagram of the composite hydrogel prepared by the application for promoting wound healing; Figure 3 The staining diagram of the composite hydrogel prepared by the application for promoting wound healing on wound healing. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application; based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.
[0011] The materials used in the following examples, such as no special instructions, are all new materials purchased in the market, wherein the SDF-1α mimetic peptide is: SDF-1 mimetic peptide-4 (SMP; LSYKCGCKFGGGFRCPCRYSL-NH2).
[0012] Example 1: The present example provides a composite hydrogel for promoting wound healing, which comprises the following raw materials by weight: 60 parts of a composite core, 3 parts of type I collagen, 8 parts of gelatin, 0.1 parts of SDF-1α mimetic peptide, 25 parts of hyaluronic acid, and 8 parts of an inclusion compound. The composite core comprises the following raw materials in a mass ratio: Bombyx mori silk: asiaticoside = 1:0.0001; The preparation method of the composite core comprises the following steps: (1) Boil Bombyx mori silk in a 0.5% sodium carbonate solution by mass volume concentration for 30 min, repeat twice to completely remove sericin, wash with deionized water, dry to form fibroin fibers, dissolve the fibroin fibers in a 9.3M lithium bromide solution, the ratio of fibroin fibers to lithium bromide solution is 1g:10mL, stir in a 60°C water bath until completely dissolved, place the solution in a dialysis bag with a molecular weight cutoff of 8kDa, dialyze in deionized water for 3 days, change the water every 4 hours to completely remove lithium bromide, finally, centrifuge the dialyzed fibroin protein solution at a speed of 9000 rpm for 20 min to remove impurities, and obtain a clear fibroin protein aqueous solution with a mass volume concentration of 6%; (2) Dissolve asiaticoside in DMSO to prepare a stock solution with a concentration of 1 mg / mL, slowly add the stock solution to the fibroin protein aqueous solution, the final concentration of asiaticoside is 10 μg / mL, magnetically stir for 2 h to mix uniformly, and form a mixed solution; (3) Place the mixed solution in the syringe of the electrospinning equipment, electrospinning molding, set the process parameters: injection speed 0.5 mL / h, voltage 15 kV, receiving distance 12 cm, control the environmental humidity at 40%, after obtaining the nanofiber membrane on the receiving plate, place it in an ethanol vapor with a volume fraction of 75% for 30 min to obtain the composite core.
[0013] The inclusion compound comprises the following raw materials in a mass ratio: hydroxypropyl-β-cyclodextrin: curcumin = 3:1; The preparation method of the inclusion compound comprises the following steps: (a) Dissolve hydroxypropyl-β-cyclodextrin in deionized water, the ratio of hydroxypropyl-β-cyclodextrin to deionized water is 1g:100mL, to form a hydroxypropyl-β-cyclodextrin solution; (b) curcumin was dissolved in anhydrous ethanol, the ratio of curcumin to anhydrous ethanol was 1 g:10 mL, then under vigorous stirring, curcumin was added dropwise into the hydroxypropyl-β-cyclodextrin solution, and continued to stir in the dark for 24 h, then filtered, freeze-dried to obtain the inclusion compound.
[0014] The embodiment also provides a preparation method of the composite hydrogel for promoting wound healing, and specifically comprises the following steps: S1, type I collagen was dissolved in 0.1% acetic acid aqueous solution, stirred overnight, and prepared into a collagen solution with a concentration of 3 mg / mL; and gelatin was dissolved in PBS, stirred and dissolved in a 37 ℃ water bath, and prepared into a gelatin solution with a concentration of 8 mg / mL; S2, the collagen solution and the gelatin solution were mixed in a volume ratio of 1:1, and stirred gently at 37 ℃ to avoid air bubbles, to form a mixed solution i; S3, SDF-1α mimetic peptide was dissolved in PBS, EDC and NHS were added as cross-linking agents, and the activated SDF-1α mimetic peptide was formed by cross-linking and activation at 4 ℃ for 30 min, the ratio of SDF-1α mimetic peptide, EDC, NHS and PBS was 5 mg:5 mg:5 mg:1 mL, the activated SDF-1α mimetic peptide was added into the mixed solution i, and slowly reacted at 4 ℃ for 12 h, so that the mimetic peptide was covalently grafted to the amino group of gelatin and collagen through amide bond, to obtain a mixed solution ii; S4, the composite core was immersed in the mixed solution ii, and was ensured to be completely covered, and then was transferred to a constant temperature environment at 37 ℃, and was placed for reaction for 1 h, and was subjected to heat-induced cross-linking, at this temperature, collagen protein was spontaneously cross-linked to form a stable network, and gelatin also played a role in assisting gelation, so that a firm stem cell recruitment layer was formed outside the core, the surface was gently washed with PBS, and a composite was obtained; S5, hyaluronic acid was dissolved in PBS to prepare a hyaluronic acid solution with a mass-volume concentration of 1%, 3-(acrylamido) phenylboronic acid, EDC and NHS were added into the hyaluronic acid solution, wherein the ratio of 3-(acrylamido) phenylboronic acid, EDC, NHS and the hyaluronic acid solution was 0.1 g:0.5 g:0.3 g:100 mL; the reaction was carried out at room temperature in the dark for 24 h, the phenylboronic acid group was grafted to the HA chain, the product was purified by dialysis, and freeze-drying was performed to obtain oxidized hyaluronic acid; S6, dissolving the oxidized hyaluronic acid and the inclusion compound in PBS to form a pre-gel solution, fully immersing the complex prepared in step S4 in the pre-gel solution, ensuring that the surface is fully and uniformly covered, after taking it out, placing it under 365 nm ultraviolet light for irradiation for 30 s, performing ultraviolet crosslinking reaction, covalently crosslinking the acrylamide groups on the oxidized hyaluronic acid chain, forming a dense and antioxidant outer layer outside the complex structure, rinsing with PBS, and then sterilizing to obtain the composite hydrogel for promoting wound healing.
[0015] Embodiment 2: The embodiment provides a composite hydrogel for promoting wound healing, the composite hydrogel for promoting wound healing comprises the following raw materials in parts by weight: 70 parts of a composite core, 5 parts of type I collagen, 10 parts of gelatin, 0.2 parts of SDF-1α mimic peptide, 30 parts of hyaluronic acid, and 10 parts of an inclusion compound. The composite core comprises the following raw materials in a mass ratio: Bombyx mori silk: asiaticoside = 1:0.00015; The preparation method of the composite core comprises the following steps: (1) boiling Bombyx mori silk in a 0.5% sodium carbonate solution for 30 min, repeating twice to completely remove sericin, washing with deionized water, and drying to form fibroin fibers; dissolving the fibroin fibers in a 9.3M lithium bromide solution, the ratio of the amount of fibroin fibers to the amount of lithium bromide solution being 1 g:10 mL, stirring in a 60°C water bath until completely dissolved, loading the solution into a dialysis bag with a molecular weight cut-off of 10 kDa, and dialyzing in deionized water for 3 days, changing the water every 6 hours to completely remove lithium bromide; finally, centrifuging the dialyzed fibroin protein solution at a speed of 9000 rpm for 20 min to remove impurities, and obtaining a clear fibroin protein aqueous solution with a mass-volume concentration of 7%; (2) dissolving asiaticoside in DMSO to prepare a stock solution with a concentration of 1.5 mg / mL, slowly adding the stock solution to the fibroin protein aqueous solution, so that the final concentration of asiaticoside is 15 μg / mL, and magnetically stirring for 2 hours to mix uniformly to form a mixed solution; (3) loading the mixed solution into a syringe of an electrospinning device, electrospinning to form a nanofiber membrane, setting the process parameters as follows: injection speed 0.8 mL / h, voltage 18 kV, receiving distance 15 cm, and environmental humidity controlled at 50%; after obtaining the nanofiber membrane on the receiving plate, placing it in an ethanol vapor with a volume fraction of 75% for 30 min to obtain the composite core.
[0016] The inclusion compound comprises the following raw materials in a mass ratio: hydroxypropyl-β-cyclodextrin: curcumin = 7:1; The preparation method of the inclusion compound comprises the following steps: (a) Dissolve hydroxypropyl-β-cyclodextrin in deionized water, the ratio of hydroxypropyl-β-cyclodextrin to deionized water is 1 g: 120 mL, to form a hydroxypropyl-β-cyclodextrin solution; (b) Dissolve curcumin in anhydrous ethanol, the ratio of curcumin to anhydrous ethanol is 1 g: 15 mL, then add the hydroxypropyl-β-cyclodextrin solution drop by drop under vigorous stirring, continue to stir in the dark for 24 h, then filter, freeze-dry to obtain the inclusion compound.
[0017] The embodiment also provides a preparation method of the composite hydrogel for promoting wound healing, and specifically comprises the following steps: S1, dissolve type I collagen in 0.1% acetic acid aqueous solution, stir overnight, prepare a collagen solution with a concentration of 5 mg / mL, and dissolve gelatin in PBS, stir and dissolve in a 37 ℃ water bath, and prepare a gelatin solution with a concentration of 10 mg / mL; S2, mix the collagen solution and the gelatin solution according to a volume ratio of 1:1, gently stir at 37 ℃ to avoid air bubbles, and form a mixed solution i; S3, dissolve SDF-1α mimic peptide in PBS, add EDC and NHS as cross-linking agents, activate for 30 min at 4 ℃, form activated SDF-1α mimic peptide, the ratio of SDF-1α mimic peptide, EDC, NHS and PBS is 5 mg: 7 mg: 5 mg: 1-2 mL, add the activated SDF-1α mimic peptide to the mixed solution i, and slowly react for 12 h at 4 ℃, so that the mimic peptide is covalently grafted to the amino group of gelatin and collagen through an amide bond, to obtain a mixed solution ii; S4, immerse the composite core in the mixed solution ii, ensure complete coverage, then transfer it to a constant-temperature environment at 37 ℃, and stand for reaction for 1 h to perform heat-induced cross-linking, at this temperature, collagen spontaneously cross-links to form a stable network, and gelatin also plays a role in auxiliary gelation, so that a firm stem cell recruitment layer is formed outside the core, wash the surface with PBS, and obtain a composite; S5, dissolve hyaluronic acid in PBS to prepare a hyaluronic acid solution with a mass-volume concentration of 1%, add 3-(acrylamido) phenylboronic acid, EDC and NHS to the hyaluronic acid solution, wherein the ratio of 3-(acrylamido) phenylboronic acid, EDC, NHS and the hyaluronic acid solution is 0.12 g: 0.5 g: 0.3 g: 100 mL; react for 24 h at room temperature in the dark, graft the phenylboronic acid group to the HA chain, dialyze and purify, and freeze-dry to obtain oxidized hyaluronic acid; S6, dissolving the oxidized hyaluronic acid and the inclusion compound in PBS to form a pre-gel solution, fully immersing the complex prepared in step S4 in the pre-gel solution, ensuring that the surface is fully and uniformly covered, after taking it out, placing it under 365 nm ultraviolet light for irradiation for 60 s, performing ultraviolet crosslinking reaction, covalently crosslinking the acrylamide groups on the oxidized hyaluronic acid chain, forming a dense and antioxidant outer layer outside the complex structure, rinsing with PBS, and then sterilizing to obtain the composite hydrogel for promoting wound healing.
[0018] Example 3: The composite hydrogel for promoting wound healing provided in this example includes the following raw materials by weight: 80 parts of a composite core, 8 parts of type I collagen, 15 parts of gelatin, 0.3 parts of SDF-1α mimic peptide, 35 parts of hyaluronic acid, and 15 parts of an inclusion compound. The composite core includes the following raw materials by mass ratio: Bombyx mori silk: asiaticoside = 1:0.0002; The preparation method of the composite core includes the following steps: (1) Boil Bombyx mori silk in a 0.5% sodium carbonate solution by mass volume concentration for 30 min, repeat twice to completely remove sericin, wash with deionized water, and dry to form fibroin fibers. Dissolve the fibroin fibers in a 9.3M lithium bromide solution, with a dosage ratio of 1 g:10 mL, stir in a 60°C water bath until completely dissolved, place the solution in a dialysis bag with a 14 kDa molecular weight cut-off, and dialyze in deionized water for 3 days, changing the water every few hours to completely remove lithium bromide. Finally, centrifuge the dialyzed fibroin protein solution at 9000 rpm for 20 min to remove impurities, and obtain a clear fibroin protein aqueous solution with a mass volume concentration of 8%; (2) Dissolve asiaticoside in DMSO to prepare a stock solution with a concentration of 2 mg / mL. Slowly add the stock solution to the fibroin protein aqueous solution, with a final concentration of asiaticoside of 20 μg / mL. Stir magnetically for 2 h to ensure uniform mixing, forming a mixed solution; (3) Place the mixed solution in the syringe of the electrospinning equipment. Set the process parameters as follows: injection speed 0.1 mL / h, voltage 20 kV, receiving distance 20 cm, and environmental humidity controlled at 50%. After obtaining the nanofiber membrane on the receiving plate, place it in an ethanol vapor with a volume fraction of 75% for 30 min to obtain the composite core.
[0019] The inclusion compound includes the following raw materials by mass ratio: hydroxypropyl-β-cyclodextrin: curcumin = 10:1; The preparation method of the inclusion compound includes the following steps: (a) Dissolve hydroxypropyl-β-cyclodextrin in deionized water, the ratio of hydroxypropyl-β-cyclodextrin to deionized water is 1 g: 150 mL, to form a hydroxypropyl-β-cyclodextrin solution; (b) Dissolve curcumin in anhydrous ethanol, the ratio of curcumin to anhydrous ethanol is 1 g: 20 mL, then add the hydroxypropyl-β-cyclodextrin solution drop by drop under vigorous stirring, continue to stir in the dark for 24 h, then filter, freeze-dry to obtain the inclusion compound.
[0020] The embodiment also provides a preparation method of the composite hydrogel for promoting wound healing, and specifically comprises the following steps: S1, dissolve type I collagen in 0.1% acetic acid aqueous solution, stir overnight, prepare a collagen solution of 8 mg / mL, dissolve gelatin in PBS, stir and dissolve in a 37 ℃ water bath, prepare a gelatin solution of 15 mg / mL; S2, mix the collagen solution and the gelatin solution according to a volume ratio of 1:1, gently stir at 37 ℃ to avoid air bubbles, to form a mixed solution i; S3, dissolve SDF-1α mimic peptide in PBS, add EDC and NHS as cross-linking agents, activate for 30 min at 4 ℃, to form activated SDF-1α mimic peptide, the ratio of SDF-1α mimic peptide, EDC, NHS and PBS is 5 mg: 10 mg: 5 mg: 2 mL, add the activated SDF-1α mimic peptide to the mixed solution i, slowly react for 12 h at 4 ℃, so that the mimic peptide is covalently grafted to the amino group of gelatin and collagen through amide bond, to obtain a mixed solution ii; S4, immerse the composite core into the mixed solution ii, ensure complete coverage, then transfer it to a constant temperature environment at 37 ℃, stand for 1 h of heat-induced cross-linking, at this temperature, collagen spontaneously cross-links to form a stable network, and gelatin also plays a role in auxiliary gelation, so that a firm stem cell recruitment layer is formed outside the core, gently wash the surface with PBS, to obtain a composite; S5, dissolve hyaluronic acid in PBS, prepare a hyaluronic acid solution with a mass-volume concentration of 1%, add 3-(acrylamido) phenylboronic acid, EDC and NHS to the hyaluronic acid solution, wherein the ratio of 3-(acrylamido) phenylboronic acid, EDC, NHS and the hyaluronic acid solution is 0.15 g: 0.5 g: 0.3 g: 100 mL; react for 24 h at room temperature in the dark, graft the phenylboronic acid group to the HA chain, dialysis purification, freeze-drying, to obtain oxidized hyaluronic acid; S6, dissolving the oxidized hyaluronic acid and the inclusion compound in PBS to form a pre-gel solution, immersing the composite prepared in step S4 into the pre-gel solution, ensuring that the surface is fully and uniformly covered, after taking it out, placing it under 365 nm ultraviolet light for irradiation for 90 s, performing ultraviolet crosslinking reaction, covalently crosslinking the acrylamide groups on the oxidized hyaluronic acid chain, forming a dense and antioxidant outer layer outside the composite structure, rinsing with PBS, and then sterilizing to obtain the composite hydrogel for promoting wound healing.
[0021] Comparative Example 1 differs from Example 2 in that the composite core is not added, and the rest is exactly the same as Example 2.
[0022] Comparative Example 2 differs from Example 2 in that the inclusion compound is not added, and the rest is exactly the same as Example 2.
[0023] Comparative Example 3 differs from Example 2 in that the SDF-1α mimetic peptide is not added, and the rest is exactly the same as Example 2.
[0024] Experimental Example: 1. Cell toxicity HUVECs were plated in a 96-well plate, and the cells were incubated with complete medium for 24 hours to wait for cell adhesion. The cells were incubated with the composite hydrogel for promoting wound healing prepared in Examples 1-3 and Comparative Examples 1-3 of the present application in a CO2 cell incubator for 24 hours, and then washed with sterile buffer three times. Then 450 μL of fresh culture medium and 50 μL of cell counting reagent-8 (CCK-8) reaction solution were added to each well, and the cells were again placed in a CO2 cell incubator for incubation for about 2 hours. The absorbance of each well at 450 nm was measured by an enzyme-labeled instrument, the corresponding data was recorded, and the cell survival rate was calculated. The results are shown in Table 1.
[0025] 2. The representative bacteria of gram-positive bacteria and gram-negative bacteria, Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), were selected to evaluate the antibacterial performance. The composite hydrogel for promoting wound healing prepared in Examples 1-3 and Comparative Examples 1-3 of the present application was added to 5.00 mL of bacterial solution (bacterial solution concentration was 1.00×107 CFUs / mL), and was placed in a 37.0℃ shaking bed for co-culture for 6 hours, with a speed of 150 rpm. Subsequently, each group of bacterial solution was diluted by 1.00×105 times, and was further uniformly coated on Luria Broth agar plate culture medium, and was placed in a culture box for culture for 24 hours, and the number of bacteria was counted. The antibacterial rate of each group was calculated according to the following formula: R = [(N0-N) / N0×100%, and the results are shown in Table 1.
[0026] 3. Wound healing rate The 6-week-old female BALB / c mice were selected for the experiment and randomly divided into the groups of Examples 1-3 and Comparative Examples 1-3. First, acute full-thickness skin wounds of about 8 mm were made on the backs of all the mice after the hairs were removed. Then, the prepared pre-cooled composite hydrogel solution was uniformly sprayed on the wound sites. The administration was performed immediately after the injury and again on the first day after the injury. The wounds were observed and measured at specific time points, and the wound area was calculated using Image J software. The wound healing rate was calculated according to the formula: wound healing rate = (S original wound - S remaining wound) / S original wound x 100%, and the results are recorded in Table 1. The skin tissue samples of the mice were collected 4. Anti-inflammatory in vitro The composite hydrogel for promoting wound healing prepared by Examples 1-3 and Comparative Examples 1-3 of the present application was used as a sample. The RAW264.7 cells in the logarithmic growth phase were adjusted to a cell suspension with a density of 5 x 104 cell / mL, and then 1 mL of the suspension was added to each well of a 12-well cell culture plate. After the cells were cultured in the incubator, the original culture medium was discarded and 1 mL of the corresponding new culture medium and sample extract (2 mg / mL) was added. The cells were incubated in the incubator for 2 h, and then a LPS solution with a final concentration of 1 μg / mL was added and transferred to the incubator for continuous culture for 24 h. After the culture was completed, the cell supernatant was collected for inflammatory factor detection. Standard preparation, sample incubation and resuspension were performed, and then detection analysis was performed on a flow cytometer. The cytokine standard was transferred to a 2 mL centrifuge tube, and the standard was diluted by Assay Diluent to a total volume of 300 μL. A centrifuge tube containing only 300 μL of Assay Diluent was used as the zero well. The capture microspheres were mixed well in advance, and then the microspheres, samples and PE-labeled cytokine detection antibodies were mixed in a volume ratio of 1:1:1, and incubated at room temperature for 2 h in the dark. Detection was performed. 100 μL of wash buffer was added to each centrifuge tube, mixed well, and then the device was placed in the flow cytometer for detection. The results are shown in Figure 1
[0027] Table 1: Test results of the performance of the composite hydrogel for promoting wound healing
[0028] As shown in the results of Table 1, the cell survival rate of all groups was higher than 95%, indicating that the entire preparation system had good biocompatibility, and the addition of each component did not introduce cytotoxicity. The antibacterial rate of Comparative Example 2 was significantly lower than that of the other groups, proving that the addition of the inclusion compound enhanced the antibacterial properties of the composite hydrogel for promoting wound healing. The wound healing rate of Examples 1-3 reached 99.4%, indicating that the composite core, inclusion compound and other substances added in the present application provided a good environment for promoting wound healing.
[0029] Figure 1 The figure of quantitative analysis of positive expression of TNF-α, IL-6 and IL-10 shows that the expression of TNF-α and IL-6 inflammatory factors of the group of example 2 is far lower than that of the untreated blank group, and meanwhile, the expression of IL-10 of the group of Shishili 2 is far higher than that of the blank group, which indicates that the prepared composite hydrogel for promoting wound healing has good anti-inflammatory capacity, and provides favorable conditions for wound healing. Figure 2 The figure of quantitative analysis of positive expression of TNF-α, IL-6 and IL-10 shows that the expression of TNF-α and IL-6 inflammatory factors of the group of example 2 is far lower than that of the untreated blank group, and meanwhile, the expression of IL-10 of the group of Shishili 2 is far higher than that of the blank group, which indicates that the prepared composite hydrogel for promoting wound healing has good anti-inflammatory capacity, and provides favorable conditions for wound healing. Figure 3 The figure of HE staining and Masson staining of the wound tissue section of the mouse on the 7th day shows that on the 7th day, dense granulation tissue and good epithelial cells are observed in the group of example 2, while the blank group does not have this phenomenon; in the Masson staining figure, the collagen deposition of the group of example 2 is obvious, and the differentiation is obvious, while the blank group still has residual blood scab, which indicates that the prepared composite hydrogel for promoting wound healing promotes the collagen deposition of the wound of the mouse and accelerates the wound healing.
[0030] In summary, the preparation process of the composite hydrogel for promoting wound healing of the present application takes natural biological substrate as the core, and the whole process from raw material pretreatment to gradient molding not only guarantees the efficient retention of the activity of the components, but also ensures the biocompatibility of the material, providing a safe and reliable basis for wound repair. The outer layer realizes precise protection and release of active ingredients in the inflammation period with oxidation-sensitive characteristics, clearing obstacles for the repair process; the middle layer activates endogenous repair potential relying on the directional recruitment of active peptides, providing a cell basis for tissue regeneration; and the inner core realizes efficient anti-scarring repair with biomimetic structure guiding the ordered deposition of collagen. This design not only solves the multiple contradictions of infection prevention and control, inflammation regulation and tissue remodeling in wound repair, but also avoids the safety risks that may be brought by exogenous components, providing a new direction with both theoretical value and application prospect for the research and development of wound repair materials.
[0031] The above describes the present application and its embodiments, which are not restrictive, and the embodiments shown in the drawings are only one of the embodiments of the present application, and the actual application is not limited thereto. In summary, if a person skilled in the art is inspired thereby, without departing from the purpose of the present application, similar modes and embodiments are not creatively designed, which should belong to the protection scope of the present application.
Claims
1. A composite hydrogel for promoting wound healing, characterized by, The raw materials include the following components by weight: 60-80 parts of a composite core, 3-8 parts of type I collagen, 8-15 parts of gelatin, 0.1-0.3 parts of SDF-1α mimetic peptide, 25-35 parts of hyaluronic acid, and 8-15 parts of a clathrate; The composite core includes the following components by mass ratio: domestic silkworm silk: asiaticoside = 1:0.0001-0.0002; The preparation method of the composite core includes the following steps: (1) degumming and purifying domestic silkworm silk to form fibroin fibers, dissolving the fibroin fibers in a lithium bromide solution, stirring to obtain a fibroin protein aqueous solution; (2) dissolving asiaticoside in DMSO to prepare a stock solution, slowly adding the stock solution to the fibroin protein aqueous solution, and magnetically stirring to form a mixed solution; (3) electrospinning the mixed solution to form a nanofiber membrane, and then treating the nanofiber membrane with ethanol vapor to obtain the composite core.
2. The composite hydrogel according to claim 1, wherein, The clathrate includes the following components by mass ratio: hydroxypropyl-β-cyclodextrin: curcumin = 3-10:1; The preparation method of the clathrate includes the following steps: (a) dissolving hydroxypropyl-β-cyclodextrin in deionized water to form a hydroxypropyl-β-cyclodextrin solution; (b) dissolving curcumin in anhydrous ethanol, adding it to the hydroxypropyl-β-cyclodextrin solution under vigorous stirring, stirring in the dark, then filtering, and freeze-drying to obtain the clathrate.
3. The composite hydrogel of claim 1, wherein the composite hydrogel is prepared by mixing the hyaluronic acid derivative and the chitosan derivative in a ratio of 1:1 to 1:
3. In step (1), the amount ratio of the fibroin fibers to the lithium bromide solution is 1 g:10 mL; In step (3), the parameters of electrospinning are set as follows: push injection speed 0.5-1 mL / h, voltage 15-20 kV, receiving distance 12-20 cm, and environmental humidity controlled at 40-50%.
4. The composite hydrogel of claim 2, wherein the composite hydrogel is prepared by mixing the hyaluronic acid derivative and the chitosan derivative in a ratio of 1:1 to 1:
3. In step (a), the amount ratio of the hydroxypropyl-β-cyclodextrin to deionized water is 1 g:100-150 mL; In step (b), the amount ratio of the curcumin to anhydrous ethanol is 1 g:10-20 mL.
5. A method for preparing the composite hydrogel for promoting wound healing according to any one of claims 1 to 4, characterized in that, Specifically, the method includes the following steps: S1, preparing a collagen solution from type I collagen and a gelatin solution from gelatin; S2, mixing and stirring the collagen solution and the gelatin solution at a volume ratio of 1:1 to form a mixed solution i; S3, dissolving SDF-1α mimetic peptide in PBS, adding EDC and NHS for cross-linking activation to form activated SDF-1α mimetic peptide, and adding the activated SDF-1α mimetic peptide to the mixed solution i to obtain a mixed solution ii; S4, immersing the composite core in the mixed solution ii for heat-induced cross-linking to obtain a composite; S5, dissolving hyaluronic acid in PBS to prepare a hyaluronic acid solution, adding 3-(acrylamido)phenylboronic acid, EDC and NHS to the hyaluronic acid solution, avoiding light reaction, dialysis purification, and freeze-drying to obtain oxidized hyaluronic acid; S6, dissolving the oxidized hyaluronic acid and the clathrate in PBS to form a pre-gel solution, immersing the composite prepared in step S4 in the pre-gel solution, and then taking it out for ultraviolet irradiation cross-linking to obtain a composite hydrogel for promoting wound healing.
6. The method of claim 5, wherein the composite hydrogel is prepared by mixing the hyaluronic acid derivative and the alginate derivative in a ratio of 1:1 to 1:
3. In step S5, the 3-(acrylamido)benzene boronic acid, EDC, NHS and hyaluronic acid solution are used in a ratio of 0.1-0.15 g:0.5 g:0.3 g:100 mL.
Citation Information
Patent Citations
Antibacterial healing-promoting hydrogel dressing as well as preparation method and application thereof
CN114288464A
Antibacterial, anti-inflammatory and healing-promoting hydrogel dressing and preparation method thereof
CN116459387A
Sodium hyaluronate gel compound for wound repair and preparation process of sodium hyaluronate gel compound
CN119971127A
Hyaluronic acid composite hydrogel as well as preparation method and application thereof
CN120888090A
Modified hydrogel for skin wound healing and preparation method thereof
CN120960498A